Sewage long-term online ammonia nitrogen monitoring sensor based on electrochemical equilibrium
By optimizing the electrode structure and modifying the materials, the problems of signal drift and biological contamination in wastewater by the S-ISM sensor were solved, and high-precision, long-term stable online monitoring of ammonia nitrogen in wastewater was achieved.
Patent Information
- Application Number
- CN202511433626.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-09
- Publication Date
- 2025-11-07
- Estimated Expiration
- 2045-10-09
AI Technical Summary
Existing solid-state potential-selective membrane (S-ISM) sensors are prone to signal drift and biofouling problems when monitoring ammonia nitrogen in wastewater for long-term continuous monitoring, resulting in decreased detection accuracy and stability, and failing to achieve stable and accurate real-time online monitoring.
By employing a layout of reference electrode, working electrode and counter electrode on a conductive substrate, combined with POT-MWCNTs solid contact layer, ammonium ion selective membrane layer and zwitterionic copolymer coating, the potential stability is ensured by optimizing electrode structure and material modification to suppress water film formation and biofouling.
It achieves rapid response, high stability, and strong continuity in online monitoring of ammonia nitrogen in wastewater, with a monitoring accuracy of over 90%, and can perform long-term real-time monitoring in real wastewater environments.
Smart Images

Figure CN120908278A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application relates to the technical field of sewage ammonia nitrogen monitoring, and particularly relates to a sewage long-term online ammonia nitrogen monitoring sensor based on electrochemical balance. BACKGROUND
[0002] The ammonia nitrogen concentration level in sewage is widely regarded as a core index for evaluating the operation efficiency of sewage biological treatment processes (especially nitrification and denitrification processes) and judging whether the effluent water quality of a sewage treatment plant meets the standards. Real-time and accurate monitoring of the ammonia nitrogen concentration is not only a key guarantee for sewage treatment standard discharge, but also an effective way to realize intelligent control of sewage treatment plants, reduce energy consumption and reduce operation costs. At present, the precise aeration technology based on real-time online ammonia nitrogen concentration feedback control has gradually matured. By dynamically adjusting the aeration intensity, aeration time and carbon source dosage and other operation parameters, the aeration energy consumption and the consumption of additional carbon sources can be significantly reduced, thereby meeting the strict emission standards while achieving significant economic and environmental benefits. This intelligent control mode based on real-time monitoring meets the current increasingly stringent risk control requirements for sewage discharge.
[0003] However, the current widely used ammonia nitrogen analysis methods, such as the traditional Nessler's reagent colorimetric method, ion chromatography, spectrophotometry and the like, although have high sensitivity and reliability, generally have the outstanding defects of complex and tedious analysis process, time-consuming and laborious sample pretreatment, strong dependence on instruments and equipment and the like. In addition, these laboratory analysis methods generally require manual sampling and laboratory analysis, and the detection feedback cycle is long (usually several hours or even several days), resulting in obvious lack of timeliness of the analysis results. At the same time, due to the many manual operation links, operation errors or human biases are easily introduced, causing poor repeatability and stability of the detection results. Therefore, these methods are difficult to provide real-time, accurate and reliable water quality data for the automatic operation control module of the sewage treatment plant, and cannot timely and effectively support the instantaneous decision-making and dynamic regulation and control requirements in the sewage treatment process, seriously restricting the further development of sewage treatment process optimization. Therefore, it is urgent to develop an electrochemical potential sensor for online detection of ammonia nitrogen with strong stability and high precision, so as to realize real-time monitoring of precise and long-term sewage ammonia nitrogen.
[0004] Solid-state ionophore selective electrode (S-ISM) sensors have been widely used in many fields due to their low detection limit, no need for external power supply, fast response, and low cost. S-ISM sensors can achieve trace detection limits as low as micrograms per liter (μg / L). Meanwhile, the solid-state structure avoids the problems of leakage, volatilization, and inconvenience of maintenance of the internal filling liquid of traditional liquid-state potential-type electrodes. However, there are still some technical bottlenecks in the current S-ISM sensor technology. First, S-ISM sensors are prone to signal drift during long-term continuous monitoring, which is due to the formation of a water film between the electrode membrane and the solid contact interface, leading to a decrease in the stability of the potential reading. Second, in actual complex water environments such as sewage and groundwater, biofilm attachment (biofouling) on the electrode surface can further reduce sensitivity and accuracy, and even cause the electrode to fail within a few days.
[0005] Currently, some studies have introduced conductive polymer materials (such as multi-walled carbon nanotubes (MWCNTs) and conductive polymers (PEDOT)) between the S-ISM sensor membrane and the solid electrode contact layer. These methods can reduce the interface resistance and inhibit the formation of an interface water film to some extent, but they cannot fundamentally solve the problem of biofouling during long-term use of S-ISM sensors. In addition, the long-term stability of these conductive materials in wastewater is also a challenge. For example, MWCNTs may agglomerate, and conductive polymers may gradually degrade or have a decrease in electrochemical stability, resulting in a significant decrease in reliability during long-term continuous monitoring. The method of modifying the hydrophilicity of the electrode membrane surface (such as introducing polyethylene glycol (PEG), graphene oxide (GO), or silicon dioxide (SiO2) nanoparticles) can effectively reduce the attachment and pollution of microorganisms and their metabolites on the electrode surface. However, the enhancement of the hydrophilicity of the S-ISM sensor membrane surface can lead to the adsorption and retention of more water molecules, exacerbating the formation of a water layer between the membrane and the solid electrode contact interface, resulting in a significant drift in the potential reading of the electrode. This signal drift phenomenon is particularly pronounced during long-term continuous monitoring, thereby severely restricting the accuracy and stability of the electrode during long-term use. Therefore, it is urgent to develop a S-ISM ammonia nitrogen electrochemical potential sensor that can simultaneously inhibit the formation of a water film and biofouling to achieve stable and accurate real-time online monitoring of wastewater ammonia nitrogen. SUMMARY
[0006] In view of the above problems, the present application provides a long-term online ammonia nitrogen monitoring sensor for wastewater based on electrochemical equilibrium.
[0007] The technical solution of the present application is: The application discloses a long-term online ammonia nitrogen monitoring sensor for sewage based on electrochemical balance, which comprises a conductive substrate, a reference electrode, a working electrode and a counter electrode are sequentially arranged on the upper surface of the conductive substrate from one side to the other side along the width direction, the front ends of the reference electrode, the working electrode and the counter electrode extend to the front end edge of the conductive substrate, and the rear ends of the reference electrode, the working electrode and the counter electrode extend to the rear part of the conductive substrate along the length direction and jointly form an electrochemical reaction working area, wherein an extension area arranged at the rear end of the working electrode serves as a contact area, and the rear end of the counter electrode surrounds the contact area. A POT-MWCNTs solid contact layer is arranged above the contact area, an ammonium ion selective membrane layer is arranged above the POT-MWCNTs solid contact layer, and a zwitterionic copolymer coating layer is arranged above the ammonium ion selective membrane layer.
[0008] Further, the reference electrode, the working electrode and the counter electrode are arranged at equal intervals, the working electrode is located at the center of the conductive substrate, the reference electrode, the working electrode and the counter electrode are in contact with wires on the side close to the front end of the conductive substrate, an elongated transition zone is arranged between the wire contact zone and the electrochemical reaction working area, and the area on the upper surface of the conductive substrate, except the electrochemical reaction working area, is encapsulated by a dielectric protective paint.
[0009] Description: By reasonably arranging the reference electrode, the working electrode and the counter electrode, the monitoring process can be ensured to be stable and fast.
[0010] Further, the length of the conductive substrate is 35-40 mm, the width is 10-15 mm, and the thickness is 0.5-1 mm, and the contact area is circular.
[0011] Description: By reasonably controlling the size of the conductive substrate, the overall portability can be improved under the premise of ensuring the monitoring effect.
[0012] Further, the material of the conductive substrate is glass carbon plate or dense graphite sheet.
[0013] Description: By selecting a suitable material of the conductive substrate, the conductivity and excellent physical properties can be ensured.
[0014] Further, the reference electrode, the working electrode and the counter electrode are printed on the conductive substrate by a screen printing technology, and the printing method is as follows: first, the conductive substrate is cleaned by ultrasonic for 15-20 min, dried, and then 1-2 times of carbon ink printing is performed at the position of the working electrode, the total printing thickness is 8-20 µm, and drying and curing are performed at a temperature of 80-120 ℃ for 10-20 min; 1 time of AgCl ink printing is performed at the position of the reference electrode, the printing thickness is 8-20 µm, and drying and curing are performed at a temperature of 80-120 ℃ for 10-20 min; and 1-2 times of platinum ink printing is performed at the position of the counter electrode, the total printing thickness is 8-20 µm, and drying and curing are performed at a temperature of 80-120 ℃ for 10-20 min.
[0015] Description: By reasonably controlling the printing parameters of each electrode, the printing position can be ensured to be accurate.
[0016] Further, the preparation method of the POT-MWCNTs solid contact layer is as follows: 3-4 mg of multi-walled carbon nanotubes is added into 1-2 mL of poly(3-octylthiophene-2,5-diyl), dispersed in 1-2 mL of tetrahydrofuran solution, and ultrasonic treatment is performed for 30-60 s, the obtained suspension is centrifuged at a centrifugal speed of 18,000-20,000 rpm for 10-15 min, the separated solid material POT-MWCNTs is redispersed in 1-2 mL of tetrahydrofuran as a POT-MWCNTs suspension, and 10-15 µL of the POT-MWCNTs suspension is dropped on the surface of the conductive substrate and evaporated at room temperature.
[0017] Description: The preparation method of the POT-MWCNTs solid contact layer of the application optimizes the ion flow in the electrode and reduces the leaching rate of the ion carrier, has the advantage of guaranteeing the stability of the potential response, and the prepared POT-MWCNTs solid contact layer is uniform and dense and has a stable structure.
[0018] Further, the preparation method of the ammonium ion selective membrane layer is as follows: 6.5-7 parts of dodecaoxacyclo compound C 40 H 64 O 12 , 92-93 parts of a plasticizer, and 0.5-1 part of tetraoctylammonium chloride are uniformly mixed to obtain a selective membrane mixture, then the selective membrane mixture is mixed with 49-51 parts of polyvinyl chloride, and the mixture is uniformly mixed in 148-152 parts of tetrahydrofuran by ultrasonic treatment to obtain an ammonium ion selective membrane solution, the ammonium ion selective membrane solution is drop-coated on the POT-MWCNTs solid contact layer, and the ammonium ion selective membrane layer is obtained by drying at room temperature and in the dark for 36-48 h, and the plasticizer is dibutyl phthalate.
[0019] Description: By introducing the dodecaoxadicyclic compound C 40 H 64 O 12 As the carrier of ammonium ion, the carbonyl group thereof reacts with the ammonium ion in a tetrahedral configuration, achieving high selective recognition and response to target ions.
[0020] Further, the ammonium ion selective membrane layer is further added with PTFE hydrophobic modified particles, and the preparation method of the ammonium ion selective membrane layer added with the PTFE hydrophobic modified particles is as follows: polytetrafluoroethylene nanoparticles are uniformly dispersed in a tetrahydrofuran solution, and a uniformly mixed dispersion liquid is prepared after ultrasonic treatment for 10-15 min, the mass concentration of the dispersion liquid is 4-5%, the dispersion liquid and the ammonium ion selective membrane liquid are mixed according to a volume ratio of 1:1, then the mixture is uniformly drop-coated on the surface of the POT-MWCNTs solid contact layer, and the mixture is dried at room temperature under light-proof conditions for 36-48 h to obtain the ammonium ion selective membrane layer.
[0021] Description: By adding polytetrafluoroethylene PTFE hydrophobic modified particles to modify the surface of the electrode, the negative charge and roughness of the surface of the electrode are effectively reduced, the hydrophobicity of the electrode is improved, thereby inhibiting the formation of water film and the hindering effect of water layer penetration on electron transfer.
[0022] Further, the preparation method of the zwitterionic copolymer coating is as follows: the zwitterionic copolymer is prepared into an aqueous solution with a mass concentration of 0.5±0.05%, the zwitterionic copolymer is uniformly coated on the surface of the ammonium ion selective membrane layer by drop-coating or dip-coating, and the zwitterionic copolymer is naturally dried at room temperature for 24-36 h to form a hydrophilic nanochannel coating.
[0023] Description: By introducing the zwitterionic copolymer coating, the growth of the biofilm can be inhibited.
[0024] Further, the zwitterionic copolymer is trifluoroethyl methacrylate or sulfobetaine methacrylate.
[0025] Description: Trifluoroethyl methacrylate or sulfobetaine methacrylate has a good inhibiting effect on the biofilm.
[0026] The beneficial effects of the present application are as follows: The present application introduces the dodecaoxadicyclic compound C 40 H 64 O 12As the carrier of ammonium ion, the carbonyl group thereof acts with ammonium ion in a tetrahedral configuration, realizing high selective recognition and response to target ions. Meanwhile, the surface of the electrode is modified by polytetrafluoroethylene (PTFE), effectively reducing the negative charge and roughness of the electrode surface and improving the hydrophobicity thereof, thereby inhibiting the formation of water film and the hindering effect of water layer penetration on electron transfer. In combination, a POT-MWCNTs solid-state contact layer structure is designed, optimizing the ion flow in the electrode and reducing the leaching rate of the ion carrier, ensuring the stability of the potential response. Finally, a self-assembled zwitterionic copolymer coating is introduced, which inhibits biofilm growth by forming a stable hydration layer and maintaining the electrical neutrality of the electrode surface, and constructs a hydrophilic nanochannel with a pore size of about 1 nm, balancing the electric coulomb driving force between the ion layer and the charge layer at the electrode interface in the sewage environment, ensuring the ion flux and potential stability, and significantly reducing signal drift. Ultimately, a long-term online ammonia nitrogen monitoring sensor for sewage is obtained, which has rapid response, stability, high efficiency and strong sustainability. BRIEF DESCRIPTION OF DRAWINGS
[0027] Figure 1 is a schematic diagram of the overall structure of a long-term online ammonia nitrogen monitoring sensor for sewage based on electrochemical balance according to the present application; Figure 2 is a top view of a long-term online ammonia nitrogen monitoring sensor for sewage based on electrochemical balance according to the present application; Figure 3 is a cross-sectional view of the contact area of a long-term online ammonia nitrogen monitoring sensor for sewage based on electrochemical balance according to the present application; Figure 4 is a schematic diagram of the ion selection mechanism and stability and balance optimization of a long-term online ammonia nitrogen monitoring sensor for sewage based on electrochemical balance according to the present application; Figure 5 is the six-month monitoring data of the electrochemical potential of the sensor in the experimental example of the present application.
[0028] Among them, 1 is a conductive substrate, 11 is a wire contact strip, 12 is a transition strip, 2 is a reference electrode, 3 is a working electrode, 4 is a counter electrode, 5 is an electrochemical reaction working area, 51 is a contact area, 6 is a POT-MWCNTs solid-state contact layer, 7 is an ammonium ion selective membrane layer, and 8 is a zwitterionic copolymer coating. DETAILED DESCRIPTION
[0029] Example 1: A long-term online ammonia nitrogen monitoring sensor for sewage based on electrochemical balance, as shown in Figure 1As shown, it comprises a conductive substrate 1, the length of the conductive substrate 1 is 37 mm, the width is 12 mm, and the thickness is 0.8 mm. The material of the conductive substrate 1 is glass carbon plate. The upper surface of the conductive substrate 1 is sequentially provided with a reference electrode 2, a working electrode 3 and a counter electrode 4 from one side to the other side along the width direction. The front ends of the reference electrode 2, the working electrode 3 and the counter electrode 4 all extend to the front end edge of the conductive substrate 1, and the rear ends extend to the rear part of the conductive substrate 1 along the length direction and jointly constitute an electrochemical reaction working area 5. Among them, the extension area provided at the rear end of the working electrode 3 serves as a contact area 51, as shown in Figure 2 The rear end of the counter electrode 4 surrounds the contact area 51. The contact area 51 is circular. The reference electrode 2, the working electrode 3 and the counter electrode 4 are arranged at equal intervals. The working electrode 3 is located at the center of the conductive substrate 1. The reference electrode 2, the working electrode 3 and the counter electrode 4 are wire contact strips 11 near the front end of the conductive substrate 1. The transition zone 12 between the wire contact strips 11 and the electrochemical reaction working area 5 is in the shape of an elongated strip. The area on the upper surface of the conductive substrate 1 except the electrochemical reaction working area 5 is encapsulated with dielectric protective paint. The reference electrode 2, the working electrode 3 and the counter electrode 4 are printed on the conductive substrate 1 by screen printing technology. The printing method is as follows: first, the conductive substrate 1 is cleaned by ultrasonic cleaning for 16 min, dried, and then 1 time of carbon ink printing is performed at the position of the working electrode 3 with a printing thickness of 15 µm. The printed layer is cured by drying at a temperature of 100 ℃ for 15 min. 1 time of AgCl ink printing is performed at the position of the reference electrode 2 with a printing thickness of 15 µm. The printed layer is cured by drying at a temperature of 100 ℃ for 15 min. 1 time of platinum ink printing is performed at the position of the counter electrode 4 with a printing thickness of 12 µm. The printed layer is cured by drying at a temperature of 100 ℃ for 15 min. As shown in Figure 1 and Figure 3 The contact area 51 is provided with a POT-MWCNTs solid contact layer 6 above it. An ammonium ion selective membrane layer 7 is provided above the POT-MWCNTs solid contact layer 6. An amphoteric ion copolymer coating layer 8 is provided above the ammonium ion selective membrane layer 7. The preparation method of the POT-MWCNTs solid contact layer 6 is as follows: 3.5 mg of multi-walled carbon nanotubes (MWCNTs) is added into 1.5 mL of poly(3-octylthiophene-2,5-diyl) (POT), dispersed in 1.5 mL of tetrahydrofuran solution, and treated by a probe-type ultrasonic instrument for 45 s. The obtained suspension is centrifuged at a centrifugal speed of 19000 rpm for 12 min. The separated solid material POT-MWCNTs is redispersed in 1.5 mL of tetrahydrofuran as a POT-MWCNTs suspension. 12 µL of the POT-MWCNTs suspension is dropped on the surface of the conductive substrate 1 and evaporated at room temperature. The preparation method of the ammonium ion selective membrane layer 7 is as follows: 6.9 parts of dodecaoxacyclo compound C 40 H 64 O 12 , 92.4 parts of plasticizer dibutyl phthalate, and 0.7 parts of tetraoctylammonium chloride are uniformly mixed to obtain a selective membrane mixture, then the selective membrane mixture is mixed with 50 parts of polyvinyl chloride, and is uniformly mixed in 150 parts of tetrahydrofuran under ultrasonic treatment to obtain an ammonium ion selective membrane solution. The preparation method of the zwitterionic copolymer coating layer 8 is as follows: a zwitterionic copolymer is prepared into an aqueous solution with a mass concentration of 0.5%, and is uniformly coated on the surface of the ammonium ion selective membrane layer 7 by drop coating, and is naturally dried at room temperature for 30 hours to form a hydrophilic nanochannel coating with a pore size of about 1 nm, and the zwitterionic copolymer is trifluoroethyl methacrylate. The room temperature is 25°C.
[0030] Example 2: The difference between this example and example 1 is that the preparation method of the ammonium ion selective membrane layer 7 is as follows: 6.9 parts of dodecaoxacyclo compound C 40 H 64 O 12 , 92.4 parts of plasticizer dibutyl phthalate, and 0.7 parts of tetraoctylammonium chloride are uniformly mixed to obtain a selective membrane mixture, then the selective membrane mixture is mixed with 50 parts of polyvinyl chloride, and is uniformly mixed in 150 parts of tetrahydrofuran under ultrasonic treatment to obtain an ammonium ion selective membrane solution. The polytetrafluoroethylene nanoparticles are uniformly dispersed in a tetrahydrofuran solution, and a uniformly mixed dispersion liquid is prepared after ultrasonic treatment for 12 minutes, and the mass concentration of the dispersion liquid is 4.5%. After the dispersion liquid and the ammonium ion selective membrane solution are mixed in a volume ratio of 1:1, the mixture is uniformly drop coated on the surface of the POT-MWCNTs solid contact layer 6, and is dried at room temperature and in the dark for 40 hours to obtain the ammonium ion selective membrane layer 7.
[0031] Example 3: The difference between this example and example 1 is that the conductive substrate 1, the length of the conductive substrate 1 is 35 mm, the width is 10 mm, and the thickness is 0.5 mm, and the material of the conductive substrate 1 is a dense graphite sheet.
[0032] Example 4: The difference between this example and example 1 is that the conductive substrate 1, the length of the conductive substrate 1 is 40 mm, the width is 15 mm, and the thickness is 1 mm, and the material of the conductive substrate 1 is a glassy carbon plate.
[0033] Note: The size of the conductive substrate 1 is kept in proportion, and both the glassy carbon plate and the dense graphite sheet have conductive properties and excellent physical properties.
[0034] Example 5: The difference between this example and Example 1 is that the reference electrode 2, the working electrode 3 and the counter electrode 4 are printed on the conductive substrate 1 by a screen printing technique. The printing method is as follows: first, the conductive substrate 1 is cleaned by ultrasonic for 15 min, dried, and then 1 time of carbon ink printing is performed at the position of the working electrode 3, with a printing thickness of 8 pm, and dried and cured at a temperature of 80°C for 10 min; 1 time of AgCl ink printing is performed at the position of the reference electrode 2, with a total printing thickness of 8 pm, and dried and cured at a temperature of 80°C for 10 min; 1 time of platinum ink printing is performed at the position of the counter electrode 4, with a printing thickness of 8 pm, and dried and cured at a temperature of 80°C for 10 min.
[0035] Example 6: The difference between this example and Example 1 is that the reference electrode 2, the working electrode 3 and the counter electrode 4 are printed on the conductive substrate 1 by a screen printing technique. The printing method is as follows: first, the conductive substrate 1 is cleaned by ultrasonic for 20 min, dried, and then 2 times of carbon ink printing is performed at the position of the working electrode 3, with a total printing thickness of 20 pm, and dried and cured at a temperature of 120°C for 20 min; 1 time of AgCl ink printing is performed at the position of the reference electrode 2, with a printing thickness of 20 pm, and dried and cured at a temperature of 120°C for 20 min; 2 times of platinum ink printing is performed at the position of the counter electrode 4, with a total printing thickness of 20 pm, and dried and cured at a temperature of 120°C for 20 min.
[0036] Note: The parameters of the screen printing technique for the reference electrode 2, the working electrode 3 and the counter electrode 4 can be reasonably adjusted within the given parameter range.
[0037] Example 7: The difference between this example and Example 1 is that the preparation method of the POT-MWCNTs solid contact layer 6 is as follows: 3 mg of multi-walled carbon nanotubes is added to 1 mL of poly(3-octylthiophene-2,5-diyl), dispersed in 1 mL of tetrahydrofuran solution, and ultrasonically treated for 30 s. The obtained suspension is centrifuged at a centrifugal speed of 18000 rpm for 10 min, and the separated solid material POT-MWCNTs is re-dispersed in 1 mL of tetrahydrofuran as a POT-MWCNTs suspension. 10 pL of the POT-MWCNTs suspension is dropped on the surface of the conductive substrate 1, and evaporated at room temperature.
[0038] Example 8: The difference between this example and Example 1 is that the preparation method of the POT-MWCNTs solid-state contact layer 6 is as follows: 4 mg of multi-walled carbon nanotubes is added to 2 mL of poly(3-octylthiophene-2,5-diyl), dispersed in 2 mL of tetrahydrofuran solution, and ultrasonically treated for 60 s. The obtained suspension is centrifuged at a centrifugal speed of 20,000 rpm for 15 min. The separated solid material POT-MWCNTs is redispersed in 2 mL of tetrahydrofuran as a POT-MWCNTs suspension. 15 μL of the POT-MWCNTs suspension is dropped on the surface of the conductive substrate 1, and evaporated at room temperature.
[0039] Note: The parameters of the electrochemical deposition method in the preparation of the POT-MWCNTs solid-state contact layer 6 can be reasonably adjusted within the given parameter range.
[0040] Example 9: The difference between this example and Example 2 is that the polytetrafluoroethylene nanoparticles are uniformly dispersed in a tetrahydrofuran solution, and a uniformly mixed dispersion is prepared after ultrasonic treatment for 10 min. The mass concentration of the dispersion is 4%.
[0041] Example 10: The difference between this example and Example 2 is that the polytetrafluoroethylene nanoparticles are uniformly dispersed in a tetrahydrofuran solution, and a uniformly mixed dispersion is prepared after ultrasonic treatment for 15 min. The mass concentration of the dispersion is 5%.
[0042] Note: The parameters in the preparation of the PTFE hydrophobic modified particles can be reasonably adjusted within the given parameter range.
[0043] Example 11: The difference between this example and Example 1 is that the preparation method of the ammonium ion selective membrane layer 7 is as follows: 6.5 parts of dodecaoxacyclo compound C 40 H 64 O 12 , 92 parts of plasticizer dibutyl phthalate, and 0.5 parts of tetraoctylammonium chloride are uniformly mixed to obtain a selective membrane mixture. Then, the selective membrane mixture is mixed with 49 parts of polyvinyl chloride in 148 parts of tetrahydrofuran, and ultrasonically mixed uniformly to obtain an ammonium ion selective membrane solution. The ammonium ion selective membrane solution is drop-coated on the POT-MWCNTs solid-state contact layer 6, and dried at room temperature in the dark for 36 h to obtain the ammonium ion selective membrane layer 7.
[0044] Example 12: The difference between this example and Example 1 is that the preparation method of the ammonium ion selective membrane layer 7 is as follows: 7 parts of dodecaoxacyclo compound C 40 H 64 O 12, 93 parts of a plasticizer dibutyl phthalate, 1 part of tetraoctylammonium chloride are uniformly mixed to obtain a selective membrane mixture, then the selective membrane mixture is mixed with 51 parts of polyvinyl chloride, and is uniformly mixed in 152 parts of tetrahydrofuran under ultrasonic mixing to obtain an ammonium ion selective membrane solution, the ammonium ion selective membrane solution is drop-coated on the POT-MWCNTs solid-state contact layer 6, and is dried at room temperature in the dark for 48 h to obtain an ammonium ion selective membrane layer 7.
[0045] Description: The ammonium ion selective membrane layer 7 is the main innovation of the application, and the parameters in the preferred embodiment 1 or embodiment 2 have the optimal effect.
[0046] Embodiment 13: The difference between this embodiment and embodiment 1 is that the preparation method of the zwitterionic copolymer coating 8 is as follows: the zwitterionic copolymer is prepared into an aqueous solution with a mass concentration of 0.45%, is uniformly coated on the surface of the ammonium ion selective membrane layer 7 by drop coating, and is naturally dried at room temperature for 24 h to form a hydrophilic nanochannel coating, and the zwitterionic copolymer is trifluoroethyl methacrylate.
[0047] Embodiment 14: The difference between this embodiment and embodiment 1 is that the preparation method of the zwitterionic copolymer coating 8 is as follows: the zwitterionic copolymer is prepared into an aqueous solution with a mass concentration of 0.55%, is uniformly coated on the surface of the ammonium ion selective membrane layer 7 by dip coating, and is naturally dried at room temperature for 36 h to form a hydrophilic nanochannel coating, and the zwitterionic copolymer is sulfobetaine methacrylate.
[0048] Description: The zwitterionic copolymer trifluoroethyl methacrylate or sulfobetaine methacrylate has high chemical stability and good inhibition effect on the attachment of biological membranes.
[0049] Experimental example: The long-term online ammonia nitrogen monitoring sensor for sewage based on electrochemical equilibrium prepared in embodiment 1 is applied in a real sewage environment to monitor ammonia nitrogen in the sewage, for example Figure 4 As can be seen, the NH4 + First diffuses in water, passes through the nanochannels (about 1 nm) formed by the zwitterionic copolymer coating 8 to the surface of the ammonium ion selective membrane layer 7, and the zwitterionic copolymer coating 8 blocks the attachment and penetration of biological pollutants, then the NH4 + is combined with the matrix of the ammonium ion selective membrane layer 7 to form charge separation on both sides of the ammonium ion selective membrane layer 7, and the PTFE hydrophobic modified particles effectively prevent water from penetrating into the ammonium ion selective membrane layer 7 to affect the NH4 + is combined with the matrix of the ammonium ion selective membrane layer 7; Subsequently, the ion charges accumulated at the interface of the ammonium ion selective membrane layer 7 are converted into an electronic chemical potential difference through the POT-MWCNTs solid-state contact layer 6, the electronic chemical potential difference is collected through the conductive substrate 1, transmitted to the electrochemical workstation through the wire connected to the front end of the working electrode 3, and the open circuit voltage signal collected is processed, such as Figure 5 As shown in the figure, the abscissa is time, and the ordinate is the NH4 + concentration converted from the voltage signal, the law shown represents the dynamic change of the NH4 + concentration with time, reflecting the stability of the ammonia nitrogen signal; The long-term online ammonia nitrogen monitoring sensor based on the electrochemical equilibrium of the application can achieve an ammonia nitrogen monitoring accuracy of more than 90% in sewage, far exceeding the existing commercial in-situ ion sensor (accuracy less than 50%), and can realize real-time in-situ monitoring for up to one month in a real sewage environment.
Claims
1. A long-term on-line ammonia nitrogen monitoring sensor for sewage based on electrochemical equilibrium, characterized in that, The application relates to an electrochemical sensor, which comprises a conductive substrate (1), a reference electrode (2), a working electrode (3) and a counter electrode (4) arranged on the upper surface of the conductive substrate (1) from one side to the other side along the width direction, the front ends of the reference electrode (2), the working electrode (3) and the counter electrode (4) extend to the front end edge of the conductive substrate (1), and the rear ends extend to the rear part of the conductive substrate (1) along the length direction and jointly form an electrochemical reaction working area (5), wherein an extension area arranged at the rear end of the working electrode (3) is used as a contact area (51), and the contact area (51) is surrounded by the rear end of the counter electrode (4). A POT-MWCNTs solid contact layer (6) is arranged above the contact area (51), an ammonium ion selective membrane layer (7) is arranged above the POT-MWCNTs solid contact layer (6), and a zwitterionic copolymer coating layer (8) is arranged above the ammonium ion selective membrane layer (7).
2. The long-term on-line ammonia nitrogen monitoring sensor based on electrochemical balance for sewage according to claim 1, characterized in that, The reference electrode (2), the working electrode (3) and the counter electrode (4) are arranged at equal intervals, the working electrode (3) is located at the center of the conductive substrate (1), the reference electrode (2), the working electrode (3) and the counter electrode (4) are in contact with a lead wire contact strip (11) near the front end of the conductive substrate (1), an elongated transition strip (12) is arranged between the lead wire contact strip (11) and the electrochemical reaction working area (5), and the area on the upper surface of the conductive substrate (1) except the electrochemical reaction working area (5) is packaged by dielectric protective paint.
3. The long-term on-line ammonia nitrogen monitoring sensor based on electrochemical balance according to claim 1, characterized in that, The length of the conductive substrate (1) is 35-40 mm, the width is 10-15 mm, and the thickness is 0.5-1 mm, and the contact area (51) is circular.
4. The long-term on-line ammonia nitrogen monitoring sensor based on electrochemical balance according to claim 1, characterized in that, The material of the conductive substrate (1) is glass carbon plate or dense graphite sheet.
5. The long-term on-line ammonia nitrogen monitoring sensor based on electrochemical balance according to claim 1, characterized in that, The reference electrode (2), the working electrode (3) and the counter electrode (4) are printed on the conductive substrate (1) by a screen printing technology, and the printing method is as follows: firstly, the conductive substrate (1) is cleaned by ultrasonic cleaning for 15-20 min, dried, and then 1-2 times of carbon ink printing is carried out at the position of the working electrode (3), the total printing thickness is 8-20 mu m, and the printing is dried and solidified at a temperature of 80-120 DEG C for 10-20 min; AgCl ink printing is carried out at the position of the reference electrode (2) once, the printing thickness is 8-20 mu m, and the printing is dried and solidified at a temperature of 80-120 DEG C for 10-20 min; and 1-2 times of platinum ink printing is carried out at the position of the counter electrode (4), the total printing thickness is 8-20 mu m, and the printing is dried and solidified at a temperature of 80-120 DEG C for 10-20 min.
6. The long-term on-line ammonia nitrogen monitoring sensor based on electrochemical balance according to claim 1, characterized in that, The preparation method of the POT-MWCNTs solid contact layer (6) is: 3-4 mg of multi-walled carbon nanotubes is added into 1-2 mL of poly(3-octylthiophene-2,5-diyl), dispersed in 1-2 mL of tetrahydrofuran solution, and ultrasonically treated for 30-60 s; the obtained suspension is centrifuged at a centrifugal speed of 18000-20000 rpm for 10-15 min; the separated solid material POT-MWCNTs is redispersed in 1-2 mL of tetrahydrofuran to obtain a POT-MWCNTs suspension; 10-15 μL of the POT-MWCNTs suspension is dropped on the surface of the conductive substrate (1), and left to evaporate at room temperature.
7. The long-term on-line ammonia nitrogen monitoring sensor based on electrochemical balance according to claim 1, characterized in that, The preparation method of the ammonium ion selective membrane layer (7) is as follows: 6.5-7 parts of dodecaoxacyclo compound C 40 H 64 O 12 , 92-93 parts of a plasticizer, and 0.5-1 part of tetraoctylammonium chloride are uniformly mixed to obtain a selective membrane mixture, then the selective membrane mixture is mixed with 49-51 parts of polyvinyl chloride, and is uniformly mixed in 148-152 parts of tetrahydrofuran by ultrasonic mixing to obtain an ammonium ion selective membrane solution; the ammonium ion selective membrane solution is drop-coated on the POT-MWCNTs solid contact layer (6), and is dried at room temperature and in the dark for 36-48 h to obtain the ammonium ion selective membrane layer (7); the plasticizer is dibutyl phthalate.
8. The long-term on-line ammonia nitrogen monitoring sensor for sewage based on electrochemical balance according to claim 7, characterized in that, The ammonium ion selective membrane layer (7) further comprises PTFE hydrophobic modified particles. The preparation method of the ammonium ion selective membrane layer (7) comprising PTFE hydrophobic modified particles is: polytetrafluoroethylene nanoparticles are uniformly dispersed in a tetrahydrofuran solution, and a uniformly mixed dispersion liquid is prepared after ultrasonic treatment for 10-15 min, the mass concentration of the dispersion liquid is 4-5%; the dispersion liquid and the ammonium ion selective membrane liquid are mixed in a volume ratio of 1:1, and then uniformly dropped and coated on the surface of the POT-MWCNTs solid contact layer (6); and the ammonium ion selective membrane layer (7) is obtained after drying at room temperature and in dark for 36-48 h.
9. The long-term on-line ammonia nitrogen monitoring sensor based on electrochemical balance according to claim 1, characterized in that, The preparation method of the zwitterionic copolymer coating layer (8) is: a zwitterionic copolymer is prepared into an aqueous solution with a mass concentration of 0.5±0.05%, and the zwitterionic copolymer coating layer (8) is formed by uniformly coating the zwitterionic copolymer on the surface of the ammonium ion selective membrane layer (7) through drop coating or dip coating, and naturally drying at room temperature for 24-36 h.
10. The long-term on-line ammonia nitrogen monitoring sensor for sewage based on electrochemical balance according to claim 9, characterized in that, The zwitterionic copolymer is trifluoroethyl methacrylate or sulfobetaine methacrylate.
Citation Information
Patent Citations
Method for detecting ammonia nitrogen by means of all-solid-state ammonia nitrogen sensor and device thereof
CN105738452A
Ammonium ion sensor and preparation method thereof
CN115856035A
High-sensitivity ammonium ion electrochemical sensor and application thereof
CN116465947A
AgNPs, QCs and zwitter-ion-based coating material with synergistic antibacterial and anti-pollution functions and preparation method of AgNPs, QCs and zwitter-ion-based coating material
CN118697943A